(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article contains thoughts on the socio-pedagogical necessity of developing the perceptive abilities of future teachers, the importance of pedagogical-psychological theories in the formation of professional skills, and the activities of great people who have a role in the formation of our spirituality. , opinions about the requirements imposed on them are stated. V dannoy state izlagayutsya mysli o sotsialno-pedagogicheskoy neobhodimosti razvitiya poznavatelnyx kobnostey budushchich uchiteley, znachenii pedagogo-psychologicheskix teoriy v formationi professionalnogo masterstva, deyatelnosti velikix lyudey, obladyushchix samodostatochnostyu v formationi nashe dukhovnoe mnenie o trebovaniyax, pred'yavlyaemyx k nim. In this article, thoughts on the socio-pedagogical necessity of developing the perceptive abilities of future teachers, the importance of pedagogical-psychological theories in the formation of professional skills, the activities of great people who have self-sufficiency in the formation of our spirituality opinions about the demands placed on them.